2013
DOI: 10.1073/pnas.1304960110
|View full text |Cite
|
Sign up to set email alerts
|

Distinct antimicrobial peptide expression determines host species-specific bacterial associations

Abstract: Animals are colonized by coevolved bacterial communities, which contribute to the host's health. This commensal microbiota is often highly specific to its host-species, inferring strong selective pressures on the associated microbes. Several factors, including diet, mucus composition, and the immune system have been proposed as putative determinants of host-associated bacterial communities. Here we report that species-specific antimicrobial peptides account for different bacterial communities associated with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
305
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 277 publications
(322 citation statements)
references
References 65 publications
12
305
4
1
Order By: Relevance
“…In other systems ranging from hydra to fish and mice, closely related hosts harbor more similar microbial communities than do more distantly related individuals (Zoetendal et al, 2001;Friswell et al, 2010;Navarrete et al, 2012;Faith et al, 2013;Franzenburg et al, 2013). The ongoing discovery of particular loci that shape the gut microbiome in model organisms (Benson et al, 2010) presents an intriguing target for future studies across animal systems in both the lab and field.…”
Section: Drivers Of Natural Microbiome Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other systems ranging from hydra to fish and mice, closely related hosts harbor more similar microbial communities than do more distantly related individuals (Zoetendal et al, 2001;Friswell et al, 2010;Navarrete et al, 2012;Faith et al, 2013;Franzenburg et al, 2013). The ongoing discovery of particular loci that shape the gut microbiome in model organisms (Benson et al, 2010) presents an intriguing target for future studies across animal systems in both the lab and field.…”
Section: Drivers Of Natural Microbiome Compositionmentioning
confidence: 99%
“…Across mammalian species, host phylogeny and diet correlate with the structure and diversity of gut bacterial communities (Ley et al, 2008). The concordance of gut microbiota and host phylogeny suggests hostderived factors can strongly shape the taxonomic composition of the gut microbiome (Rawls et al, 2006;Franzenburg et al, 2013), whereas dietary correlations reflect, partially, the importance of gut bacteria in the use of different foods. Yet, the types of consumed foods can mediate the influence of host-derived genetic factors on gut microbiota (Kashyap et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The shift in the composition of microbes was also reflected in an altered abundance of different bacterial groups (Table 1). Although microbes belonging to Oxalobacteraceae are the routinely found microbes in hydra, studies in the past have suggested that high abundance of Oxalobacteraceae in hydra polyps inoculated with foreign microbiota [5]. The precise role of Oxalobacteraceae cannot be ascertained with the available data but an increased abundance of microbes belonging to Oxalobacteraceae clearly suggests a change in the microbial composition of hydra during reproduction.…”
Section: Resultsmentioning
confidence: 97%
“…Hydra, an evolutionarily ancient multicellular organism, also harbours microbes which are believed to aid several vital processes such as immunity, cellular composition, proliferation and budding [4]. This association appears to be species-specific and is believed to be controlled by species-specific anti-microbial peptides called arminins [5]. Although Fraune and Bosch (2007) [6] showed that hydra polyps maintained in the laboratory for long periods of time exhibit similarities in microbial composition with their counterparts from the wild, a recent study suggested the influence of external environment on the microbial community structure of laboratory and wild populations of Hydra vulgaris Ind-Pune [7].…”
Section: Introductionmentioning
confidence: 99%
“…Epithelial cells produce peptides to regulate microbial communities in and on animals' bodies. Indeed, Hydra use antimicrobial peptides to control species-specific microbiomes [105,106], suggesting that antimicrobial peptides date to at least the last common ancestor of cnidarians and bilaterians and may be widespread across the animal kingdom. Given that the neurons that comprise nerve nets are interspersed among these epithelial cells, the peptides produced by epithelial cells have the potential to interfere with neuronal GPCRs.…”
Section: Could Microbes Have Played a Role In Internalization Of Nervmentioning
confidence: 99%